Immediate effects of static stretching and post isometric relaxation on hamstring flexibility among sedentary young adults: a pilot study - E., Liyanage; H. C. B., Jayasinghe; S. M. C. S., Samarakoon (International Journal Of Community Medicine And Public Health, 2022)
Background: ‘Hamstrings’ is a group of muscles in the posterior compartment of the thigh crossing both hip and knee joints. Hamstring muscles are frequently subjected to reduced flexibility, especially among young adults 18-25 years old. Hamstring tightness is found to cause several conditions affecting the human body. Stretching has immediate effects on muscle stiffness, such that, positive effects can be obtained within few seconds or minutes after a stretching session. Methods: A total of 32 Undergraduates who satisfied the inclusion criteria were recruited for the pilot study. The subjects needed to have hamstring tightness measured by active knee extension (AKE) to be included to the study. The subjects with a history of recent injury or surgery to the spine or lower limbs, those who involved in sports activity at competitive level and obese subjects were excluded. The subjects were allocated randomly by 1:1 ratio to the Static Stretching (SS) and Post Isometric Relaxation (PIR) groups. Results: The data of both the groups was normally distributed. The baseline values of AKE for both the groups (SS=46.68±5.31; PIR=49.03±6.53) were matched and there was no significant difference before stretching. Independent sample T-Test was used to compare the means of the two groups post stretching. There was a significant difference in the mean of the AKE values of the two groups. The improvement was higher in the PIR group (SS= 42.62±4.78; PIR=36.28±6.51), such that the range of flexion was lesser in the PIR group indicating a greater degree of knee extension. Conclusions: Immediate effects from single bout with few repetitions of Post Isometric Relaxation stretching were more effective in reducing hamstring tightness among sedentary young adults compared to static stretching.